Strategic Policy and Supply Chains Evaluating the Impact of the Inflation Reduction Act on U.S. Imports of EV Battery-Related Products from China - Aroka,Eveline (2025)
This thesis examines whether the Inflation Reduction Act (IRA) has reduced U.S. imports of electric vehicle (EV) battery-related products from China. The IRA, signed into law in 2022, combines consumer-side tax credits with production-side incentives to accelerate domestic EV supply chains. A core mechanism is the introduction of geographic sourcing requirements for critical battery inputs, aimed at reshaping trade flows and reducing reliance on Chinese components. To evaluate the IRA’s short-term trade impact, this study applies a Difference-in-Differences and event study design to monthly U.S. import data at the HS6 product level covering the period from April 2020 to December 2024. The treatment group consists of Chinese battery-related products targeted by the IRA’s sourcing rules, while the control group includes industrially similar but unaffected products. All models are estimated using Poisson Pseudo Maximum Likelihood (PPML) to address zero trade values and heteroskedasticity. The analysis finds no general reduction in imports of targeted products from China following the IRA’s enactment. However, one notable exception emerges: imports of lithium-ion batteries (HS 850760) increased after the policy was introduced. This pattern may reflect China’s dominant position in global battery manufacturing and the difficulty U.S. firms face in sourcing equivalent alternatives. Overall, the results suggest that the IRA’s sourcing-based incentives have not yet produced a broad-based shift away from Chinese EV battery inputs, highlighting the structural challenges of altering established supply chains through targeted policy interventions.
Keywords: Inflation Reduction Act; Electric Vehicle (EV) Batteries; Difference-in-Differences (DiD); U.S.-China Trade; Supply Chain Resilience